Permanent vocal paralysis: type I thyroplasty surgical correction - Yangali, Rubén (2008)
Permanent vocal cord paralysis causes dysphonia and repetetive aspiration episodes. We review vocal cord paralysis pathophysiology and the corrective surgical procedure known as thyroplasty